Distinctive Interactions of Oleic Acid Covered Magnetic Nanoparticles with Saturated and Unsaturated Phospholipids in Langmuir Monolayers - Matshaya, Thabo J. (2014)
The growing number of innovations in nanomedicine and nanobiotechnology are posing new challenges in understanding the full spectrum of interactions between nanomateriales and biomolecules at nano-biointerfaces. Although considerable achievements have been accomplished by in vivo applications, many issues regarding the molecular nature of these interactions are far from being well-understood. In this work, we evaluate the interaction of hydrophobic magnetic nanoparticles (MNP) covered with a single layer of oleic acid with saturated and unsaturated phospholipids found in biomembranes through the use of Langmuir monolayers. We find distinctive interactions among the MNP with saturated and unsaturated phospholipids that are reflected by both, the compression isotherms and the surface topography of the films. The interaction between MNP and saturated lipids causes a noticeable reduction of the mean molecular area in the interfacial plane, while the interaction with unsaturated lipids promotes area expansion compared to the ideally mixed films. Moreover, when liquid expanded and liquid condensed phases of the phospholipid(s) coexist, the MNP preferably partition to the liquid-expanded phase, thus hindering the coalescence of the condensed domains with increasing surface pressure. In consequence organizational information on long-range order is attained. These results evidence the existence of a sensitive composition-dependent surface regulation given by phospholipid–nanoparticle interactions which enhance the biophysical relevance of understanding nanoparticle surface functionalization in relation to its interactions in biointerfaces constituted by defined types of biomolecules.